The United States Supreme Court ruling and women's reproductive rights – A position statement issued by The European Board and College of Obstetrics and Gynaecology (EBCOG). (December 2022) - Louwen, Frank; Mukhopadhyay, Sambit; Mahmood, Tahir; Martins, Nuno Nogueira; Tarlatzis, Basil; ,
Abstract: The judicial review by the Supreme Court of the United States on Roe v. Wade has fundamentally limited the ability of women to exercise choice and control of their sexual and reproductive rights in the United States. The global organisations are concerned that there remains a risk that women's rights will be diminished globally in future.